Electrical stimulation to treat tinnitus: a meta-analysis and systemic review of randomized controlled trials - Ting Yang; Jin Zhang; Bing Wang; Wen Zhang; Min Xu; Shuangyuan Yang; Hui Liu (SAGE Publishing, 2021)
Background and aims: Tinnitus is one of the most common otological symptoms that patients experience, and it can be debilitating. No effective drug treatments are available for tinnitus, although considerable research investigating its mechanisms and possible treatments is underway. Electrical stimulation has been considered a promising and well-tolerated therapeutic strategy for tinnitus. This meta-analysis study was aimed to investigate the efficacy, safety and tolerability of electrical stimulation in patients with tinnitus. Methods: Relevant studies were retrieved from the Embase, PubMed, Web of Science, Cochrane Library, China National Knowledge Infrastructure (CNKI), Chinese Biomedical Literature (CBM), Wanfang and Weipu databases. The Tinnitus Handicap Inventory (THI) and the visual analogue scale (VAS) which focus on loudness and distress evaluation (0-10 points) were used to assess perceived tinnitus suppression after treatment. Subgroup analysis was also performed based on different stimulating areas and methods, follow-up times, tinnitus duration and electrical current intensity. Review Manager 5.4 software was used for data synthesis, and Stata 15.1 software was used for analyses of publication bias and sensitivity. Results: Our meta-analysis included 11 studies involving a total of 447 patients with tinnitus. The results showed that electrical stimulation significantly reduced THI scores [mean difference (MD) = −9.69; 95% confidence interval (CI) = −14.25, −5.13; p  < 0.0001; I 2  = 80%] and VAS scores between the two groups (VAS loudness scores, MD = −0.72; 95% CI = −1.20, −0.25; VAS distress scores, MD = −0.90; 95% CI = −1.17, −0.63). In addition, subgroup analysis showed that THI scores in electrical stimulation group of different stimulating areas and methods follow-up times, tinnitus duration and electrical current intensity were generally reduced, regardless of the acute or subacute tinnitus group or left temporoparietal area (LTA) group with no statistical significance between two groups. Conclusion: Overall, electrical stimulation may be an effective and well-tolerated treatment option for tinnitus.